UJIAN PRAKTIK IPA SUKSES DENGAN PhET COLORADO - Dwi Ning Wahyuni Budi (Madaris: Jurnal Guru Inovatif, 2022)
This best practice activity in science learning is carried out during the class IX practical exam. The purpose of the best practice activities carried out is to minimize learning loss and provide more meaningful science learning for students. A total of 110 class IX students at MTs Negeri 34 Jakarta carried out practical exam activities on February 21-25, 2022 with the practical exam material being to make series and parallel circuits using the Colorado PhET application. Practice exams are conducted offline in the Computer Lab with one day and two sessions. Each session a maximum of 19 students. The best practice implementation phase consists of three stages. The first stage is the pre-implementation, The second stage is the implementation, and the third stage is the reflection. The assessment taken has three criteria, namely the accuracy of the series and parallel circuits made, the creativity of the circuit form and the proof of Ohm's Law. Of the 110 class IX students who took the science practice exam, it was found that 93% of students correctly made the circuit, 92% of students showed a good level of creativity and 90% of students who could prove Ohm's Law with the Colorado PhET application. Thus, it can be concluded that the implementation of the science practice exam using the PhET Colorado application is a significant best practice in providing meaningful learning for students.